PEMBERDAYAAN KEWIRAUSAHAAN DAN PENGEMBANGAN UMKM MASYARAKAT KELURAHAN TAMBAK WEDI KECAMATAN KENJERAN KOTA SURABAYA - Alaric, Adrian; Adrian Pratama, Firly (Education and Talent Development Center of Indonesia, 2022)
Entrepreneurship education and MSME development as well as socialization regarding the utilization of existing opportunities are expected to improve the economy of the people of Tambak Wedi Village, Kenjeran District, Surabaya City. Through community service activities, which are routine agendas for every university, students act as problem-solving agents trying to help obstacles that arise in such a society. The method used for information collection, dissemination and implementation with supervision from students. Empowerment is carried out using participatory forms of empowerment from residents, especially women from the PKK community by way of counseling and knowledge transfer as well as understanding of proceduresand strategies in entrepreneurship and MSME development. This activity has an impact on residents who start selling on the digital market and slowly achieve economic independence.